STRATEGI KEPALA SEKOLAH DALAM MEMBANGUN BUDAYA MUTU DI LINGKUNGAN PENDIDIKAN ISLAM - Fajana, Afina; Haris, Abd (Fakultas Agama Islam Universitas Islam Madura, 2025)
Education quality management is a systematic effort to ensure that the entire education process runs effectively, efficiently, and produces quality graduates. This article aims to outline the concepts, principles, and implementation of quality management in the context of Islamic education, especially in madrasas. This study uses a library research method by examining various relevant literature, educational regulations, and previous research results. The results of the study show that education quality management includes strategic planning, resource organization, program implementation, monitoring, and continuous evaluation. Key principles of quality management include customer focus, total engagement, continuous improvement, data-driven decision-making, and systems approach. From the perspective of Islamic education, quality management is not only oriented towards achieving academic standards, but also moral development, strengthening spirituality, and developing students' character according to Islamic values. Proper implementation will produce a culture of quality in schools, improve teacher professionalism, and strengthen public trust in educational institutions. This study recommends the implementation of integrated quality management that integrates modern principles with Islamic values in order to achieve holistic and sustainable quality of education.